Treatment of Bimaxillary Protrusion by Distalization of Maxillary and Mandibular Dentitions with Extra Alveolar Bonescrews - Devender Kumar; Suchithra B K; Deeksha M (RGUHS Journal of Allied Health Sciences)
This case report describes a 21-year-old female patient presenting with skeletal Class II malocclusion an Anglersquos Class I molar relationship and an end on canine relationship bilaterally. The patient presented with a normodivergent facial pattern protruded upper and lower front teeth a convex profile competent lips a decreased nasolabial angle and posterior facial divergence. The treatment was carried out using the MBT system along with en-masse distalization facilitated by infrazygomatic crest and buccal shelf bone screws. The resulting facial changes were closely linked to the skeletal and dentoalveolar adjustments that were the focus of the treatment. In this case of borderline bimaxillary protrusion with a slightly convex profile en-masse distalization proved more effective than premolar extraction and incisor retraction. This case also serves as a valuable example of managing similar conditions effectively.